Terapi Okupasi Untuk Keterampilan Pita Rambut Pada Anak Tunagrahita - Nurlina, (Pendidikan Luar Biasa, 2008)
The general purpose of this study is to get data from the ability of mild mentally retarded student in occupational therapy through hair decoration skill in Malang Putra Jaya special education school. Knowing further the problem that are faced by the children in the ocupational process and also know the stage of achievement after get ocupational therapy thourgh hair decoration skill. Technique analysis data in this research used non statistic research in form of analysis of descriptive. In the stage of data analysis in qualitative research generally started since data collection, data reduction, displaying the data, and the conclusion verication. This research which has processed in the application of occupational therapy through hair decoration skill to mentally retarded students in the Malang Putra Jaya special school after six timestreatment which has been given. The occupational therapy shows the result that mild mentally retarded can perform the activity well and show significant result It is justified cumulatively with have sutficient category, which mentally retarded children in Malang Putra Jaya special school. The children must get a lot of practice to achive the material of hair decoration skiil in order to get increasing ability of motoric nerve movement and focusing ability of children concentration.